Policy Analysis of Clean and Healthy Living Behavior in Islamic Perspective - Munaya Fauziah; Nurmalia Lusida; Nadilla Firda; Widya Rizki Ariandini; Suherman Suherman (Indonesian Journal of Islam and Public Health, 2022)
Indonesia is a country with the largest Muslim population in the world. Islam is very pay attention to hygiene and health, so that Indonesia should become a leading country in terms of hygiene and health. Facts based on Index Southeast Asia Global Health Resilience (2019) Indonesia's health quality exists ranked 4th in Southeast Asia and ranked 30th out of 193 countries in the world. Number Maternal mortality in Indonesia in 2017 was in the 3rd highest position out of 10 countries ASEAN. To improve public health status, the Ministry of Health of The Republic of Indonesia makes a policy regarding the Guidelines for Clean Living and Healthy. This study aims to provide an understanding of Behavior Clean and Healthy Living from the perspective of Islam. Research methods using qualitative methods by analyzing 10 policy indicators Ministry of Health of the Republic of Indonesia regarding Guidelines for Clean Living Behavior and Healthy is tested for conformity with the arguments of the Qur'an and Hadith. Research result shows that 10 indicators, namely childbirth assisted by health workers, give babies exclusive breastfeeding, weigh toddlers every month, Use water clean, wash hands with soap, use healthy latrines, eradicate mosquito larvae, consuming fruits and vegetables every day, doing physical activity every day and do not smoke in the house, has the evidence of the Qur'an and Hadith. Conclusion, 10 indicators regarding Guidelines for Guidance for Clean and Healthy Living Behavior Healthy according to Islamic Sharia